Pembuatan Coupling 3 ????⁄????” Mod EU Di PT Elnusa Fabrikasi Konstruksi - Benny Haddli Irawan; Yudy Pratama; Budi Baharudin; Rahman Hakim; Hanifah Widiastuti; Widodo Widodo; Ihsan Saputra; Fedia Restu (Politeknik Negeri Batam, 2022)
Coupling 3 1⁄2” Mod EU (Modified External Upset) is an API 5CT (American Petroleum Institute) product specially made at customer's request, this product is a product that is rarely made at PT ELNUSA FABRIKASI KONSTRUKSI. In this API 5CT product, it is a Modified EU Coupling product which is designed to use an additional ring seal for extra protection on the oil-flowing pipe. To make a 3 1⁄2” Mod EU Coupling, use a CNC lathe by going through the Facing, Blanking ID, Threading ID and Grooving ID processes. The purpose of making this final project is to find out the process carried out and the use of the right method in the manufacture of 3 1⁄2” Mod EU Couplings at PT Elnusa Fabrication Construction, as a learning media or data retrieval, especially when making other Coupling products.